Analisis Standar Minimal Standing Board Jump Untuk Seleksi Atlet Bolavoli Putra Usia 17-21 Tahun - Fahmi Miftahul Murdiyanto; Achmad Widodo; Soni Sulistyarto (Jurusan Pendidikan Kesehatan dan Rekreasi, 2023)
Background: In this study the scope and objectives were to determine the leg muscle strength of volleyball athletes, the magnitude of the leg muscle values ​​of national team athletes, to find out the standard size scale used to select male volleyball athletes who will compete aged 17-21 years. Methods: This study used a qualitative descriptive method which was carried out using a standing board jump test without a prefix and the subjects were 23 volleyball athletes in Gresik Regency. Results: It was found that the selected volleyball athlete candidates must have a minimum explosive power value or leg muscle explosive power as measured by the standing board jump test = 2.35 m and have a height = 1.88 m and still be at least 17 years old and a maximum of 21 years, then the player is an ideal volleyball player candidate. By having a composition of explosive power values ​​or limb muscle explosive power as measured by the standing board jump test = 2.35 m and having a height = 1.88 m, it is hoped that these prospective players will also have high achievements like volleyball players who are members of the Volleyball Team. The Indonesian National who won the gold medal at the Sea Games in Vietnam in 2021, namely = 3.32 m, so that he will be able to do the best smash and block techniques. Furthermore, at that age, he is still able to achieve his best performance at the golden age of approximately 25 years. Conclusion: Knowing that athletes who can be included in the ranks of core players is the result of selection with standards that can be accounted for based on existing data so that players are expected to win the league they will participate in.